Analysis of the Influence of Motivation, Work Environment, Workload, Discipline, Commitment and Job Satisfaction on Employee Performance in Remote Village - Srirejeki, Dewi; Bachtiar, Yanuar; Arifin, Zainal; Sari, Erini Junita (Journal of International Conference Proceedings, 2023)
This study aims to determine the effect of motivation, work environment, workload, discipline, commitment and job satisfaction on the performance of employees at the offices of industry, trade, cooperatives and SMEs in Pulang Pisau Regency, Central Kalimantan Province, Indonesia. The study used a survey of 45 employees where this number is the population as well as the sample. The results showed that motivation, commitment and job satisfaction had a positive effect, while workload had a negative effect, while the work environment and work discipline had no effect on employee performance. Keywords: Motivation, Work Environment, Workload, Discipline, Commitment, Job Satisfaction, Employee Performance, Remote Villages